Thermal Investigation and Stereochemical Studies of Methylamine, Diethylamine and Triethylamine Complexes of Copper(II) - Nandababu Singh, L. (Asian Journal of Chemistry, 2012)
Methylamine, diethylamine and triethylamine complexes of copper(II) were synthesized. The complexes were characterized by elemental and thermal analysis, infrared and electronic spectra and magnetic moment measurement. They were found to have the following compositions: [CuL12Cl2]·5H2O, [CuL2(H2O)Cl2]·3H2O, [CuL3(H2O)Cl2]·3H2O, [CuL12Br2·2H2O and [CuL22Br2]·4H2O, where L1 = methylamine (MeA), L2 = diethylamine (DEtA) and L3 = triethylamine (TEtA). The complexes were found to be four coordinated and appear to possess square planar geometry. Thermal investigation was carried out and stereochemical changes which occurred during thermal investigations, were studied. Thermodynamic parameters such as activation energy (Ea*), enthalpy change (DH) and entropy change (DS) for dehydration and decomposition reactions of the complexes were evaluated by using some standard methods. The order of stability of the complexes (with respect to Ea* from TGA curve) follows the trend: TEtA > DEtA > MeA. The probable mechanistic path of dehydration and decomposition reactions is also shown.